Pendayagunaan dan Peran Serta Masyarakat dalam membangun Insfrastruktur sanitasi MCK - Firgina Amelia Nurhusni; Saeful Anwar; Rohmanur Aziz (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
This study aims to determine community involvement in planning, implementing and evaluating the Communal MCK sanitation facility development program in an effort to improve the quality of health managed by Odesa Indonesia in Cikadut village, Cimenyan sub-district, Bandung regency. The method in this study uses a qualitative descriptive approach as well as research and development methods. The results of this study indicate that community participation in planning the construction of communal MCK sanitation facilities can be seen from community involvement by attending and attending meetings held by community leaders to gather information about the problems being faced by the community as well as the needs of the community itself, while community participation in the implementation of development is in the form of peace. those who mobilize, for example, mutual cooperation to collect stones or building materials, land leveling and others while in the evaluation there is supervision and evaluation meetings held to assess the suitability of the development results with the plan.